Labor supply after normal retirement age in Germany A fourth pillar of retirement income? - Martina Eschelbach (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
Many European countries are currently transferring their pay-as-you-go public pension system to a three-pillar-system of public, occupational, and private pensions. In Germany, economists expect a pension gap for future retiree cohorts as public pensions will decrease and private old age provision is low. In this paper we ask, whether this pension gap might lead to the rise of a fourth pillar of retirement income: labor earnings. Using data from the German Socio-economic Panel, we find that retirees with low nonlabor income are more likely to work after normal retirement age. The negative relationship between nonlabor income and the participation probability is robust across educational and employment groups and particularly strong for retirees with low income. We conclude that labor market earnings constitute a pillar of retirement income already today.
Keywords: J22; J26; 330; old age labor supply; work after normal retirement age; fourth pillar of retirement income; Altersgrenze; Rentner; Arbeitsangebot; Gesetzliche Rentenversicherung; Rentenreform; Deutschland